Peningkatan Kapasitas Digital UMKM Simpang Odah Etam Melalui Pendekatan Web Interaktif - Rasyad, Rizky Zakariyya; Musyafa, Fahrul; Tumbel, Yosia Jeremy Ferdy; Hakim, Ayub Lukman; Rahmah, Azkia (CV. Global Cendekia Inti, 2025)
This community service project aims to enhance the digital marketing capacity of SMEs at Simpang Odah Etam (SOE) through the implementation of an interactive web based promotional platform. Using participatory methods, the team worked directly with selected vendors to conduct digital mapping and prototype development. The intervention involved observation, interviews, and the development of digital map website using AI based design tools. The result was an increased awareness among vendors of digital business strategies and a web prototype used to promote vendors locations and products. The strategy also involved collaboration with the local toursim offince and media partners to amplify reach.